1995
DOI: 10.1080/01496399508010379
|View full text |Cite
|
Sign up to set email alerts
|

Cleanup of Hydrochloric ACID Waste Streams from Actinide Processes Using Extraction Chromatography

Abstract: Extraction chromatography is under development as a method to lower actinide activity levels in hydrochloric acid (HCI) effluent steams. Successful application of this technique would allow recycle of the largest portion of HCI, while lowering the quantity and improving the form of solid waste generated.The extraction of plutonium and americium from HCI solutions was examined for several commercial and similar laboratory-produced resins coated with n-octyl(phenyl)-N,N-diisobutylcarbamoylmethylphosphine oxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…These variables include better defining the role of the phase transfer catalysts, the impact of metal contaminants present in solution on 241 Am extraction, extraction capacity for the CMPO , and DGA , extraction resins, etc. This study, and those preceding in the literature, ,,,,− , will hopefully inspire innovative research in the future that improves our general understanding of extraction chromatography. If successful, further optimizing large-scale separations for 241 Am recovery, and for processing other important analytes, will be more easily realized.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These variables include better defining the role of the phase transfer catalysts, the impact of metal contaminants present in solution on 241 Am extraction, extraction capacity for the CMPO , and DGA , extraction resins, etc. This study, and those preceding in the literature, ,,,,− , will hopefully inspire innovative research in the future that improves our general understanding of extraction chromatography. If successful, further optimizing large-scale separations for 241 Am recovery, and for processing other important analytes, will be more easily realized.…”
Section: Discussionmentioning
confidence: 70%
“…Surveying the literature revealed that others have observed similar performance from CMPO-based resins. 46,47 Often, this bimodal dependence of 241 Am K d values on HCl concentrations is attributed to hydrolysis of the m-CMPO phosphorous groups. 48 Intrigued by this phenomenon, we are mobilizing to further evaluate m-CMPO TBP , m-CMPO DAAP , and RE resin interactions with Am 3+ using macroscopic quantities of 241 Am and diagnostic spectroscopic methods.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Although the origin for this disparate performance remains unclear, it has been observed and discussed previously. 36,37 The general line shapes that described 243 Am (aq) K d dependence in HCl (aq) from the 'veteran' resins were similar to one another and to that from 'pristine' m-CMPO TBP resins. Despite these similarities, some subtle and important distinctions should be noted.…”
Section: Distribution Coefficients (K D ) From M-cmpo Tbp 'Veteran' A...mentioning
confidence: 72%
“…Although the origin for this disparate performance remains unclear, it has been observed and discussed previously. 36,37…”
Section: Resultsmentioning
confidence: 99%
“…Photoelectrooxidation of chloride ions to chlorine (Eq. 2) accompanied by water reduction at the cathode to produce H 2 , could provide an attractive, cost-effective alternative to water oxidation [8][9][10] .…”
mentioning
confidence: 99%